Difference in Level of Learning Independence Students Living in Family and Boarding Environment - Kresentia Jessica Ruron; Arief Sadjiarto (Universitas Sebelas Maret, 2020)
The environment greatly influences learning independence, especially the student environment. This study aims to determine differences in learning independence in fkip students who live in a family environment and boarding environment. This research method uses a comparative quantitative method. Data collection instrument in this study uses the scale of independence, family environment and boarding environment. The population in this study was the 2017 SWCU FKIP students, with a sample of 175 students, the sampling technique used probability sampling techniques. Data analysis method used to test the research hypothesis using Independent Samples Test. The results of data analysis showed alpha sig (2-tailed) value of 0.709 or sig value. (2-tailed)> 0.05, which means that there is no difference in the 2017 SWCU FKIP student learning independence that lives in the family environment and boarding environment